2014
DOI: 10.1215/00277630-2643839
|View full text |Cite
|
Sign up to set email alerts
|

Toric degenerations of integrable systems on Grassmannians and polygon spaces

Abstract: We introduce a completely integrable system on the Grassmannian of 2-planes in an n-space associated with any triangulation of a polygon with n sides, and compute the potential function for its Lagrangian torus fiber. The moment polytopes of this system for different triangulations are related by an integral piecewise-linear transformation, and the corresponding potential functions are related by its geometric lift in the sense of Berenstein and Zelevinsky [BZ01].

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Inspired by ideas coming from the Gelfand-Cetlin system, D. Bouloc proved in 2015 [Bou15] a similar conjecture for all singular fibers of the Kapovich-Millson system of bending flows of 3D polygons [KM96], and also of another similar integrable system studied by Nohara and Ueda [NU14] on the 2-Grassmannian manifold. Namely, he showed that all these fibers are isotropic submanifolds (if the ambient symplectic variety itself is a manifold) or orbifolds (in special situations when the ambient symplectic spaces are orbifolds but not manifolds).…”
mentioning
confidence: 82%
“…Inspired by ideas coming from the Gelfand-Cetlin system, D. Bouloc proved in 2015 [Bou15] a similar conjecture for all singular fibers of the Kapovich-Millson system of bending flows of 3D polygons [KM96], and also of another similar integrable system studied by Nohara and Ueda [NU14] on the 2-Grassmannian manifold. Namely, he showed that all these fibers are isotropic submanifolds (if the ambient symplectic variety itself is a manifold) or orbifolds (in special situations when the ambient symplectic spaces are orbifolds but not manifolds).…”
mentioning
confidence: 82%
“…For a Grassmannian Gr 2 (C n ), the plabic graphs are in bijection with triangulations of an n-gon, and in this case polytopes isomorphic to ours were obtained earlier by Nohara and Ueda. These polytopes were shown in [NU14] to be integral (unlike in the general case), and were used to construct toric degenerations of the Grassmannian Gr 2 (C n ), see also [BFF + 16].…”
mentioning
confidence: 99%
“…, r n ), which happens to be a manifold when r is generic. These moduli spaces of polygons and their bending systems have been studied from various points of views afterwards [5,6,11,12,13,17]. Our results here concern their singular fibers and state that the systems of bending flows on M r are indeed examples of systems with spherical singularities:…”
mentioning
confidence: 75%
“…After that, we prove in §5 that the singular fibers are isotropic. Finally in §6, we describe how the systems of bending flows on M r relate to integrable systems on the Grassmannian Gr(2, n) defined by Nohara and Ueda [17] and to the Gel'fand-Cetlin system on U (n). In particular we provide some arguments suggesting that the techniques employed in this paper would also apply to the integrable systems on Gr(2, n).…”
mentioning
confidence: 99%